An In Vitro Cynomolgus Vascular Surrogate System for Preclinical Drug Assessment and Human Translation. Issue 10 (October 2015) - Cole, Banumathi K.; Simmers, Michael B.; Feaver, Ryan; Qualls, Charles W.; Collado, M. Sol; Berzin, Erica; Figler, Robert A.; Pryor, Andrew W.; Lawson, Mark; Mackey, Aaron; Manka, David; Wamhoff, Brian R.; et al.
Abstract : Objectives—: The predictive value of animal and in vitro systems for drug development is limited, particularly for nonhuman primate studies as it is difficult to deduce the drug mechanism of action. We describe the development of an in vitro cynomolgus macaque vascular system that reflects the in vivo biology of healthy, atheroprone, or advanced inflammatory cardiovascular disease conditions. Approach and Results—: We compare the responses of the in vitro human and cynomolgus vascular systems to 4 statins. Although statins exert beneficial pleiotropic effects on the human vasculature, the mechanism of action is difficult to investigate at the tissue level. Using RNA sequencing, we quantified the response to statins and report that most statins significantly increased the expression of genes that promote vascular health while suppressing inflammatory cytokine gene expression. Applying computational pathway analytics, we identified statin-regulated biological themes, independent of cholesterol lowering, that provide mechanisms for off-target effects, including thrombosis, cell cycle regulation, glycogen metabolism, and ethanol degradation. Conclusions—: The cynomolgus vascular system described herein mimics the baseline and inflammatory regional biology of the human vasculature, including statin responsiveness, and provides mechanistic insight not achievable in vivo. Abstract : Supplemental Digital Content is available in the text.